Results of the long-term observational noninterventional prospective study BODYGUARD in psoriasis patients - A. L. Bakulev; D. D. Petrunin (State Scientific Center of Dermatovenereology and Cosmetology, 2019)
Introduction. Currently there is insufficient data regarding routine use of various topical treatments for plaque psoriasis outside from randomized clinical trials, their efficacy, cost-effectiveness and perception by dermatologists and patients. The primary rationale for this study was local data generation for the long-term (up to 52 weeks) treatment of body psoriasis in Russian patients' population with fixed-dose combination of calcipotriol and betamethasone dipropionate in the formulation of gel to evaluate patient's adherence to the therapy and their satisfaction level.Materials and methods. Primary study objectives were evaluation of the long-term (up to 52 weeks) treatment success of body psoriasis with fixed-dose combination of calcipotriol and betamethasone dipropionate gel by Physician (Physician Psoriasis Global Assessment (PsGA, 5-point scale)) and by patient (Patient's Global Psoriasis Assessment (PaGA, 5-point scale) and overall patient's satisfaction using 4-point scale), patient's satisfaction with the treatment via Patient Preference Questionnaire (PPQ), patients' adherence to the treatment using Questionnaire of Adherence, impact of treatment on patients' quality of life using DLQI questionnaire, and patients' readiness to buy topical therapy product out of pocket based on consumption of the study medication during follow up period. Patients received treatment with topical calcipotriol/betamethasone gel which was prescribed as a routine medication without connection to the study purposes for up to 8 weeks. After the treatment patients were followed up for up to 52 weeks; during this period they were allowed to continue treatment with either maintenance or intermittent schedule. 128 dermatologists participated in the study, 612 patients with body plaque psoriasis (mean age 42.0 ± 13.30 years) were included; from this sample 544 (88.7 %) patients underwent follow up.Results. All 612 included patients received initial therapy with calcipotriol/betamethasone gel; during follow-up period 410 (76.1 %) patients received treatment by any schedule (out of 539 assessed). Overall treatment success based on average PsGA score: initially 3.0 ± 0.54, after appr.8 weeks - 1.3 ± 0.80 and after appr.52 week 1.1 ± 0.96; based on average PaGA score - initially 3.0 ± 0.54, after appr.8 weeks - 1.5 ± 0.88 and after appr.52 week 1.1 ± 0.99. The proportion of patients which described their overall satisfaction with the treatment as "satisfied" or "absolutely satisfied" equaled 92.3 % at visit at the end of active treatment and 93.1 % at visit up to 52 weeks afterwards. Also at visit at the end of active treatment 93.8 % of patients considered their current treatment as "more effective" than previous topical treatment they received. Patients' adherence to the therapy was satisfactory - average application rate of calcipotriol/betamethasone (should be applied daily) gel at the last 7 days of treatment at visit at the end of active treatment comprised 5.6 ± 2.6 days, which means that 6 out of 7 days of the treatment were not missed. Initial DLQI score was 13.6 ± 5.95 and it reduced down to 3.89 ± 5.95 at visit at the end of active treatment (p < 0.001) reflecting positive impact of successful therapy on patients' psychosocial wellbeing.Discussion. Results of this study provides additional information regarding routine topical therapy in patients with plaque psoriasis. These findings demonstrate that the therapy of body plaque psoriasis with calcipotriol/betamethasone gel is effective both in short and long term according to the evaluation by dermatologists and by patients themselves. This therapy provides good rate of adherence and patients' satisfaction as well as affects positively at patients' psychosocial wellbeing assessed by DLQI score.